A Rapid Immunization Strategy with a Live-Attenuated Tetravalent Dengue Vaccine Elicits Protective Neutralizing Antibody Responses in Non-Human Primates - Ambuel, Yuping; Young, Ginger; Brewoo, Joseph N.; Paykel, Joanna; Weisgrau, Kim L.; Rakasz, Eva G.; Haller, Aurelia A.; Royals, Michael; Huang, Claire Y.-H.; Capuano, Saverio; Stinchcomb, Dan T.; Partidos, Charalambos D.; et al. (Frontiers in Immunology, 2014)
Dengue viruses (DENVs) cause approximately 390 million cases of DENV infections annually and over 3 billion people worldwide are at risk of infection. No dengue vaccine is currently available nor is there an antiviral therapy for DENV infections. We have developed a tetravalent live-attenuated DENV vaccine (TDV) that consists of a molecularly characterized attenuated DENV-2 strain (TDV-2) and three chimeric viruses containing the pre-membrane and envelope genes of DENV-1, -3 and -4 expressed in the context of the TDV-2 genome. To impact dengue vaccine delivery in endemic areas and immunize travelers, a simple and rapid immunization strategy (RIS) is preferred. We investigated RIS consisting of two full vaccine doses being administered subcutaneously or intradermally on the initial vaccination visit (day 0) at two different anatomical locations with a needle-free disposable syringe jet injection (DSJI) delivery devices (PharmaJet) in non-human primates (NHP). This vaccination strategy resulted in efficient priming and induction of neutralizing antibody responses to all four DENV serotypes comparable to those elicited by the traditional prime and boost (two months later) vaccination schedule. In addition, the vaccine induced CD4+ and CD8+ T cells producing IFN-γ, IL-2, and TNF-α, and targeting the DENV-2 NS1, NS3 and NS5 proteins. Moreover, vaccine-specific T cells were cross-reactive with the non-structural NS3 and NS5 proteins of DENV-4. When animals were challenged with DENV-2 they were protected with no detectable viremia, and exhibited sterilizing immunity (no increase of neutralizing titers post- challenge). RIS could decrease vaccination visits and provide quick immune response to all four DENV serotypes. This strategy could increase vaccination compliance and would be especially advantageous for travelers into endemic areas.